Odpowiedzi

2009-10-08T08:04:51+02:00
A) (a/5-a/b):a/b = (a/5-a/b)*b/a = (ab/5a)-1 = a(b/5)-1

b) (5/x-x/5):(5/x-1) = (5/x-x/5)*(x-1/5) = (5x-5/5x)-(x²-x/25) = 5(5x-5)/25x-x(x²-x)/25x=(25x-25-x³+x²)/25x

c) (a²/3b+3b-2a):3b-a/12b = (a²/6b-2a)*12b/3b-a = 12a²b/(18b²+2a²) = 2(6a²b)/2(9b²+a²)=(6a²b)/(9b²+a²)
2009-10-08T10:18:43+02:00
) (a/5-a/b):a/b=
= (a/5-a/b)*b/a =
=b/5-b²


b) (5/x-x/5):(5/x-1) =
= (5/x-x/5)*(x-1/5) =
=(x-1/x)-(x²-x/25) =
=x-1/x-x²+x/25

c) (a²/3b+3b-2a):3b-a/12b =
= a²/9b+1-2a-a/12b =
=3a²/36b+36b/36b-72ab/36b-3a/36b=
=(3a²+36b-72ab-3a):36b